Effect of Adding Alcoholic and Nano Alcoholic Extract Of Moringa Oleifera Leaves to Drinking Water on the Biochemical Blood Traits for Laying Hens Lohmann Brown - Dakhil Hasan Oraibi; Nihad Abdul –Lateef Ali (Institute of Medico-legal Publications Pvt Ltd, 2021)
This experiment was conducted at the poultry farm of the college of Agriculture, University of Al-QasimGreen the experimental field during twelve weeks from 1/ 9 / 2020 to 23/ 11/ 2020, the study was aimed toknow the effect of adding alcoholic and nano alcoholic extract of Moringa oleifera leaves to drinking wateron the biochemical blood traits for laying hens Lohmann brown. The experiment included 120 laying hensof Lohmann brown at the age of 50 weeks, the feed was provided according to the standard requirementsmentioned in the Lohmann Brown Layer Managements Guide and distributed randomly to 15 pen with 5experimental treatments for each treatment of 24 birds. Each treatment included three replicates per 8 birds.